Cytoskeletal remodeling in differentiated vascular smooth muscle is actin isoform dependent and stimulus dependent - Kim, Hak Rim (American Physiological Society, 2008)
Dynamic remodeling of the actin cytoskeleton plays an essential role in the migration and proliferation of vascular smooth muscle cells. It has been suggested that actin remodeling may also play an important functional role in nonmigrating, nonproliferating differentiated vascular smooth muscle (dVSM). In the present study, we show that contractile agonists increase the net polymerization of actin in dVSM, as measured by the differential ultracentrifugation of vascular smooth muscle tissue and the costaining of single freshly dissociated cells with fluorescent probes specific for globular and filamentous actin. Furthermore, induced alterations of the actin polymerization state, as well as actin decoy peptides, inhibit contractility in a stimulus-dependent manner. Latrunculin pretreatment or actin decoy peptides significantly inhibit contractility induced by a phorbol ester or an α-agonist, but these procedures have no effect on contractions induced by KCl. Aorta dVSM expresses α-smooth muscle actin, β-actin, nonmuscle γ-actin, and smooth muscle γ-actin. The incorporation of isoform-specific cell-permeant synthetic actin decoy peptides, as well as isoform-specific probing of cell fractions and two-dimensional gels, demonstrates that actin remodeling during α-agonist contractions involves the remodeling of primarily γ-actin and, to a lesser extent, β-actin. Taken together, these results show that net isoform- and agonist-dependent increases in actin polymerization regulate vascular contractility.